Impact of IT support system and Organizational Culture on Innovation and Job Performance: Mediating role of KM Attitude Article Sidebar - Mr. Sunil Kumar; Ms. Abha Gupta (Ramanujan International Journal of Business and Research, 2019)
The purpose of this paper is to analyze the role of information support system and organizational culture on knowledge management (KM) attitude of the organization which in turn leads to innovativeness among the employees and improve their job performance. The study uses the sample of 200 employees of the IT organizations and performs Structural Equation Modeling to assess the links between IT support, Organizational Culture (OC), KM Attitude, Innovativeness and Job Performance. Meditation of KM attitude of employees is assessed using PROCESS Macro. The study finds a significant relationship between presence of information technology support system available in the organization along with culture of the organization and level of knowledge sharing attitude among the employees of organization. Secondly, knowledge management attitude is directly related with innovation and performance of the employees. The study also establishes the mediating role of knowledge management attitude between technological support, OC with innovative competence and job performance of the employees.